Study of unconventional superconductors and breathing pyrochlore magnets - Sharma, Sudarshan (My University, 2023)
Quantum materials are solids that have unique electronic, magnetic, or optical properties arising due to quantum mechanical effects. Superconductors, topological insulators, and exotic magnets are examples of quantum materials. This thesis comprises three studies that explore the properties of four superconductors and a breathing pyrochlore magnet. In the first study, we investigate the superconducting properties of Re3B, and Re7B3 and determine the role of Re concentration and crystal inversion symmetry. Our findings reveal conventional superconductivity in both of these superconductors, despite having many ingredients for hosting unconventional superconductivity. The second study investigates the superconducting properties of non-centrosymmetric superconductors TaRuSi and TaReSi, specifically focusing on the role of spin-orbit coupling. By using density functional theory calculations, we determine the magnitude of anti-symmetric spin-orbit coupling and, using a combination of zero field and transverse field muon spin rotation /relaxation, reveal that TaRuSi hosts an unconventional superconducting state with broken time-reversal symmetry. TaReSi, however, hosts a conventional superconducting state. In the third study, we describe the synthesis and physical and magnetic properties of CuAlCr4S8, which is a breathing pyrochlore magnet. Breathing pyrochlores consist of a three-dimensional array of corner-sharing tetrahedra of alternating size formed by magnetic atoms, and their magnetic properties can be tuned by adjusting the breathing ratio. We demonstrate how CuAlCr4S8 allows for the clean realization of breathing pyrochlore physics, due to the absence of any structural transition. Overall, our studies contribute to a deeper understanding of the properties of unconventional superconductors and breathing pyrochlore magnets, revealing new insights into their exotic physics and the underlying mechanisms that govern their behaviors.
Keywords: Superconductivity; Magnetism